Performance of cocoa husk mucilage as a drag reduction agent in pipes - Hamad Khudhair, Mohammed (2011)
Energy loss during transport of fluids in an industry is one of the problems to be resolved. This research worked on the possibility of using cocoa husk mucilage as a drag reducing agent to replace synthetic polymers used by the industry today. A closed loop liquid circulation system was used to carry out the experimental work. The major variables investigated in the present work to study the effectiveness of the new drag reducer are pipe size (0.0127 m, 0.0254 m, 0.0381 m), liquid flow rate (0.5-8 m3/hr), additives concentration (100 ppm, 200 ppm and 300 ppm) and testing section length (0.5 m, 1 m, 1.5 m and 2.0 m). The extraction of the mucilage achieved by mixing 75 % ethanol and 25 % acetone for one hour and further extracted by autoclave for half an hour at 150 °c and 0.25 Mpa. Generally, the drag reduction effectiveness of the cocoa husk mucilage was proven in the present work, with a maximum percentage drag reduction value of 54.55% for the solution flowing in 0.0254 m I.D. pipe and at testing section length of 0.5 m, concentration 300 ppm and at 4 m3/hr flow rate. The cocoa bean husk mucilage concentration and the solution flow rate, showed a great effect on profile of drag reduction in the pipe. As concentration of cocoa bean husk mucilage increases, drag reduction increases in all conditions of experimental research. Besides, drag reduction is also increased by increasing flow rate until a maximum drag reduction is reached where degradation happens. The effect of pipe diameter on the percentage of drag reduction was not completely stable, generally, the 0.0254 m I.D. pipe showed the best and the most stable performance of the new mucilage as drag reducing agent. Increasing the testing section length led to the reduction in the cocoa husk mucilage effectiveness as a drag reducer due to continues effect of shear force on the mucilage molecules with length. A numerical empirical expression was developed depending on the experimental data. The numerical model major equation was f = a (Re)b. Several solutions and models were introduced for each case of drag reduction in the present work depending on the experimental system investigated. As a conclusion; a new environmental friendly drag reducing agent is successfully introduced and its effectiveness in improving the flow was proven experimentally.